Abdominal Circumference as a Predictor of Blood Pressure Increase in Menopausal Women in the Mengwi District - Dewi, Kadek Ayu Rosita; Winaya, I Made Niko; Tianing, Ni Wayan; Utama, Anak Agung Gede Eka Septian (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : Abdominal circumference serves as an indicator in determining central obesity criteria. In the Asia-Pacific region, the central obesity criteria are abdominal circumference ?90 cm for men and ?80 cm for women. Menopausal women experience decreased estrogen levels associated with the loss of subcutaneous fat and increased abdominal fat. When there is excessive fat distribution in the central body, there is a possibility of decreased adiponectin levels as an anti-atherogenic factor, leading to increased blood pressure. This study aims to determine the relationship between abdominal circumference and blood pressure increase in menopausal women in the Mengwi District. Method : A cross-sectional study was conducted on a population of menopausal women aged 45-55 years using a consecutive sampling technique. Subjects were selected according to inclusion, exclusion, and dropout criteria until the total number of subjects reached 85 individuals. Data analysis was performed using the Spearman rho test to determine the relationship between variables and the correlation strength. Results : Based on the data analysis, there was a significant relationship between abdominal circumference and blood pressure, as evidenced by a p-value of 0.018 (p<0.05) and a weak positive correlation coefficient (0.255). Conclusion : Abdominal circumference is associated with increased blood pressure in menopausal women with a weak correlation level.   Keywords: abdominal circumference, blood pressure, women, menopause